2022
DOI: 10.3389/fphar.2022.783506
|View full text |Cite
|
Sign up to set email alerts
|

Bilobalide Exerts Anti-Inflammatory Effects on Chondrocytes Through the AMPK/SIRT1/mTOR Pathway to Attenuate ACLT-Induced Post-Traumatic Osteoarthritis in Rats

Abstract: Although osteoarthritis (OA) significantly affects the quality of life of the elderly, there is still no effective treatment strategy. The standardized Ginkgo biloba L. extract preparation has been shown to have a wide range of therapeutic effects. Bilobalide, a unique ingredient of Ginkgo biloba, has anti-inflammatory and antioxidant pharmacological properties, but its mechanism of action on OA remains unknown. In this study, we investigated the effects of bilobalide on the development of OA through in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…In addition, autophagy inhibitor 3-MA was used to incubate IL-1β-treated chondrocytes to demonstrate the role of autophagy in osthole-mediated attenuation of OA-related degeneration. The expression of LC3 II protein and mRNA in chondrocytes treated with IL-1β for 24 h was decreased, whereas the expression of p62 was increased relative to controls, which was consistent with a previous report [ 17 ]. Similarly, immunofluorescence staining data showed that the level of LC3 II in IL-1β-treated chondrocytes was significantly reduced, as was the number of APs.…”
Section: Resultssupporting
confidence: 93%
“…In addition, autophagy inhibitor 3-MA was used to incubate IL-1β-treated chondrocytes to demonstrate the role of autophagy in osthole-mediated attenuation of OA-related degeneration. The expression of LC3 II protein and mRNA in chondrocytes treated with IL-1β for 24 h was decreased, whereas the expression of p62 was increased relative to controls, which was consistent with a previous report [ 17 ]. Similarly, immunofluorescence staining data showed that the level of LC3 II in IL-1β-treated chondrocytes was significantly reduced, as was the number of APs.…”
Section: Resultssupporting
confidence: 93%
“…Recent evidence has suggested that autophagy stabilizes the chondrocyte extracellular matrix, increases anabolism, but decreases catabolism, apoptosis, and ROS production [ 12 , 38 ]. Several studies have shown that mTOR signaling is involved in the activation of autophagy in chondrocytes in OA [ 36 , 39 , 40 ]. Inhibition of the activity of mTOR improves autophagy by directly phosphorylating the serine sites of ULK1, an important regulatory protein for autophagy induction [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo biloba L. has anti-inflammatory effects on human articular chondrocytes and OA rats ( Chen et al, 2013 ). The main components of Ginkgo biloba L. extract, bilobalide and ginkgolide B, have been reported to reverse OA ( Hu et al, 2018 ; Mao et al, 2019 ; Ma et al, 2022a ). However, the biological function of GC on cartilage has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are recent discoveries in the chemistry and mechanism of action of compounds in Ginkgo biloba L. extract ( Ma et al, 2022a ; Zhang R. et al, 2022 ; Samec et al, 2022 ). However, not many reports highlight the benefit of GC on degenerative cartilage diseases.…”
Section: Introductionmentioning
confidence: 99%